Genetics of ischaemic stroke. Issue 12 (25th April 2013) - Sharma, Pankaj; Yadav, Sunaina; Meschia, James F
Abstract : Recent advances in genomics and statistical computation have allowed us to begin addressing the genetic basis of stroke at a molecular level. These advances are at the cusp of making important changes to clinical practice of some monogenic forms of stroke and, in the future, are likely to revolutionise the care provided to these patients. In this review we summarise the state of knowledge in ischaemic stroke genetics particularly in the context of how a practicing clinician can best use this knowledge.